External Morphology of the Eggs of Some Lappet Moths (Lepidoptera, Lasiocampidae) - Долинская, И.В.; Плющ, И.Г. (Вестник зоологии, 2000)
Eggs of 9 species belonging to 5 genera of Lasiocampidae were examined with the use of scanning electron microscopy. Descriptions and comparative morphological analysis are provided for all these species. As a result, all the examined species are divided into 2 groups and 2 subgroups; the diagnostic characters for genera and species are chosen. С помощью электронного сканирующего микроскопа изучены яйца 9 видов Lasiocampidae, относящиеся к 5 родам. Выделены диагностические признаки для родов и видов. Проведена оценка значимости признаков. На основании сравнительно-морфологического анализа все исследуемые виды разделены на 2 группы и 2 подгруппы.